The effect of adding natural wastes on some properties of gypsum: تأثير إضافة المخلفات الطبيعية على بعض خواص الجبس - Alaa Ahmad Zohir Kattan, Nada Altonji, Fatima Alsaleh (Journal of engineering sciences and information technology, 2021)
In this research, the effect of adding some natural wastes to gypsum was studied in order to use them as thermal insulation materials in buildings and to recycle these wastes. Thermal insulation panels were installed from gypsum (as a basic material) and natural wastes (sawdust, peanut shells, wheat straw, cottonwood) at percentages (10, 15, 20) %, and some of their mechanical and physical properties, and their thermal conductivity were studied. The results indicated an improvement in some properties of gypsum after adding wastes, and obtaining thermal building materials that have better properties than the reference sample (gypsum) in some cases. Rough sawdust samples (SdR15, SdR20) achieved the highest compressive strength exceeding (4MPa). The flexural strength was for peanut shells samples (P10:1.76 MPa, P15:1.8 MPa), while the most efficient samples as thermal insulation were ground straw and smooth sawdust samples (SdS15, SdS20, GSt15, GSt20) where their thermal conductivity was (0.194-0.141W/m.K), which makes it acceptable according to the Syrian thermal insulation code.